Measuring the level of leanness of production - use of production lead time - Medonos, Michal; Jurová, Marie (Univerzita Pardubice, 2017)
To manage any company process, it is essential to measure its performance. Lean production as a process of a change in a production, which is one of the main company processes, is no exception. We see that the universal methodology of a practically applicable evaluation of the level of leanness of production is missing. Many authors use some form of qualitative methodology - especially in form of questionnaires. In this paper, we focus on an analysis of possible approach using a quantitative methodology. We take Little's Law formula describing direct correlation between lead time and work in process to use lead time as a main metric to evaluate leanness of production. Thanks to the formula, we know that the shorter the production time is, the less buffers are kept and the more effective and thus the “leaner” the material flow is. As a benchmark for ideal lean company, we use one piece flow representing the top level of lean production.
Keywords: lean manufacturing; performance measurement; Little's Law; lead time; M11